Adaptation of polish law on higher education to the european union requirements - Hryshchuk Yuliia (Borys Grinchenko Kyiv Metropolitan University, 2016)
The article examines the process of adapting Polish Law on Higher Education to the requirements of the European Union. It analyzes the main methods of adapting Polish law to European (Translation of European law into Polish, checking compliance of regulations to European law, work on laws aimed at adapting Polish law to European) and the role of public authorities in this process. An important novelty of Higher Education of Poland was the introduction of European standards and State qualifications that lead to fundamental changes in the methods and design of training programs based on learning outcomes. Created effective mechanisms of integration into the European community contributed to the development of higher education in accordance with the applicable EU legislation. The updated Law on Education regulates compliance system of higher education in the Bologna process. Provisions of the law allowed to switch the two cycle training scheme bachelor - master and implement the European credit transfer system. The main provisions of European programs and documents have been successfully implemented in Polish legislation that contributed to the development of partnerships in European higher education space. It is concluded, that for the 1991-2004 period almost complete compliance of national legislation with the acquis communautaire has been achieved in the field of education. International recognition, investment increase in the education sector, the European Community support suggest the successful implementation of the Republic of Poland of its obligations, as a member of the EU, in higher education transnational policy.